The influence of rater empathy, age and experience on writing performance assessment - Alp, Pilvi; Epner, Anu; Pajupuu, Hille (LingBaW. Linguistics Beyond and Within, 2017)
Assessment reliability is vital in language testing. We have studied the influence of empathy, age and experience on the assessment of the writing component in Estonian Language proficiency examinations at levels A2–C1, and the effect of the rater properties on rater performance at different language levels. The study included 5,270 examination papers, each assessed by two raters. Raters were aged 34–73 and had a rating experience of 3–15 years. The empathy level (EQ) of all 26 A2–C1 raters had previously been measured by Baron-Cohen and Wheelwright’s self-report questionnaire. The results of the correlation analysis indicated that in case of regular training (and with three or more years of experience), the rater’s level of empathy, age and experience did not have a significant effect on the score.